Kualitas Kimia Daging Ayam Broiler dengan Suhu Pemeliharaan yang Berbeda - Siskha Nurul Hidayah; Hanny Indrat Wahyuni; Sri Kismiyati (Universitas Sulawesi Barat, 2019)
The aim of this study is to prove the influence of different rearing temperature on the chemical quality of broiler chickens meat. Twenty birds of male broiler chicken CP 707 strain age 21 days was used in this study. The average body weight was 1 167±0,17 g. The research used t-test with 2 treatments and 10 replications. The treatments applied was rearing temperature: high (35-36ºC, T1) and standart (23-24ºC, T2) from age 21 - 35 days. The variables observed were moisture, ash, fat and protein content of thebreast meat. The results showed that different rearing temperature did not significantly affected on the moisture and ash content, but significantly affected on the fat and protein content of broiler breast meat (P<0.05). The conclusions of this study was proved that high rearing temperature (35-36ºC) from 21 to 35 days of age caused a decreased in protein content and an increased in fat content of breast broiler chickens meat, however, the moisture and ash content remained similar.